PRARANCANGAN PABRIK METIL MERKAPTAN DARI METANOL DAN HIDROGEN SULFIDA DENGAN KAPASITAS 30.000 TON/TAHUN - , SAMUEL A. SIMATUPANG; , Ir. Moh. Fahrurrozi, M.Sc, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This methyl mercaptan plant is designed with capacity of 30,000 tons per year. Methyl Mercaptan can be used as raw material of methionine that used as cattle food additive and as jet fuel additive. It is produced by reacting methanol and hydrogen sulfide in a fixed bed multitubular reactor. This plant produces methyl mercaptan 99,91 % as main product. Methyl mercaptan plant from methanol and hydrogen sulfide is a high risk plant, due to the use of high temperature and pressure. Furthermore methyl mercaptan is poisonous and flammable. Besides, there is no methyl mercaptan plant in Indonesia. This plant needs 2.661,64 kg per hours of methanol with 99% concentration and 2.158,77 kg per hours of hydrogen sulfide with a minimum of 99% concentration. Utilities needed include 71.954,93 kg per hours of water, 38754,97 kg per hours of steam with 1 atm pressure, and 718,08 kVA of electricity. This plant will be built in 2015 at Balikpapan on 48.114 m2 land, including office building and development area. The plant will be operated 24 hours per day and 330 days per year with 186 labors. The fixed capital investment is $ 15,597,815.33 + Rp 8.643.976.608,81 and the working capital investment is $ 7,464,044.47 + Rp 70.222.490.218,30 The economic evaluation shows that the return on investment (ROI), before tax 49,01 % and after tax 24,50 %, the pay out time (POT) before tax 1,69 years and after tax 2,9 years, the break even point (BEP) 39,46 %, the shut down point (SDP) 24,90 % and the discounted cash flow of rate of return, DCFRR 28,09 %. Considering the results of economic analysis above, the methyl mercaptan plant from methanol and hydrogen sulfide with 30,000 tons per year capacity is feasible to be built.